AKIBAT HUKUM TERHADAP PENOLAKAN PEMBATALAN PERDAMAIAN DALAM PENUNDAAN KEWAJIBAN PEMBAYARAN UTANG: Legal Consequences of Refusal of Peace Cancellation in Delaying Debt Payment Obligations - Aprilianti , Putri; Sanusi, Heru Pringgodani (Faculty of Law, Universitas Trisakti, 2025)
If a peace agreement has been homologated by the Commercial Court, it is found that the debtor has breached his contract or is negligent in implementing the contents of the peace agreement (default), then the creditor can submit a request to cancel the peace agreement. One of the decisions of the Central Jakarta Commercial Court rejected the creditors' application for the cancellation of the peace agreement which had been homologated, so that it had legal consequences for the creditors. The issue being discussed is what the legal consequences of refusing to cancel the homologated peace agreement will be on the creditors. The method used is a normative research method, which is descriptive in nature, comes from secondary and primary data, and draws conclusions deductively. The legal consequence of refusing to cancel a peace agreement is that creditors do not have certainty regarding the settlement of debts and receivables between creditors and debtors, and this results in creditors experiencing financial losses because they do not receive debt payments from debtors.